PERANCANGAN DAN IMPLEMENTASI DATA LOSS PREVENTION SYSTEM DENGAN MENGGUNAKAN NETWORK ATTACHED STORAGE - Defni, S.Si, M.Kom; Cipto Prabowo, MT (ITP Press, 2013)
There was no denying the data security issues deserved to be become a problem that must be solved. Data is one of thing which has become a reference for people to take a decision. Currently most of companies, colleges, and other institutions also rely on the data in their operations. It also the data is a very important part. In order that to preventing data losses, we are designed a system called Data Loss Prevention System which is a system that can be realize the client computer data backup scenarios are done on a scheduled basis. The backup data will be deposited on the infrastructure or Network Attached Storage (NAS) server computer so that a centralized data storage. In the processing of retrieving data from the server to the client computer, the system uses a protocol called Rsync.